Peran Sentral Pemahaman Kimia Terhadap Pengembangan Energi Terbarukan - Zamza, Nuri Indria Khofidatus (Maliki Interdisciplinary Journal, 2025)
Renewable energy offers a sustainable solution to Indonesia’s energy needs and plays a crucial role in environmental preservation. This study aims to understand the role of chemistry in renewable energy development and the challenges faced in Indonesia. The method used is a descriptive-qualitative approach based on library research, analyzing primary sources from previous studies on the production and utilization of renewable energy such as solar, wind, biomass, hydro, and geothermal. Results show that chemistry is instrumental in innovating materials and technology for renewable energy processing and storage. However, challenges such as limited raw materials, technological constraints, and low policy support remain major obstacles. Cross-sector collaboration is suggested as a solution to overcome these barriers and accelerate the adoption of sustainable renewable energy technologies in Indonesia.